Bridging the gap between brand experience and customer loyalty: The mediating role of emotional-based trust - Ong, Chuan Huat (International Academic Research Journal, 2015)
In the business arena, every manager hopes to prolong their business lifespan through customer loyalty. Therefore, it is important to understand the predictor and influence of customer trust in order to strengthen the customer-brand relationship.Customer trust is formed from rational and emotional perspective.However, the latter trust is less studied despite being argued to be more stable as compared to rational-based trust.This study aims to investigate how emotional-based trust can influence customer loyalty in the customer-brand relationship context.Loyalty is examined separately as attitudinal and behavioural in order to provide clearer insight on customer-brand relationship. This study seeks to examine three research issues: (1) Does emotional based trust influence both attitudinal and behavioural loyalty? (2) Does brand experience influence emotional based trust? and (3) Does emotional-based trust mediate the relationship between brand experience and both dimensions of loyalty? 220 surveys were obtained from intercept survey from customer on Small and Medium Enterprise (SME) brand in the restaurant industry. Result shows that there is a positive relationship between brand experience and on emotional-based trust, on emotional-based trust and both attitudinal and behavioural loyalty, and on emotional-based trust mediates the linkage between brand experience and loyalty.